Environmental, social, and governance practices and perceived tail risk. (6th October 2019) - Shafer, Michael; Szado, Edward
Abstract: Using the implied volatility smirk on individual equity securities to measure perceived tail risk, we find that better environmental, social and governance (ESG) practices significantly reduce ex‐ante expectations of a left‐tail event. Our findings are robust to using multiple model specifications and to adjusting for potential endogeneity concerns. We also show that, while practices in each ESG pillar are important in reducing perceived tail risk, the environmental pillar plays the most important role. Our results indicate that investors consider strong ESG practices to be insurance against left‐tail events rather than wasteful investment borne out of managers' own values or self‐interest.